OCT-MoS, a dataset of mouse skin squamous cell carcinoma stages by full-field optical coherence tomography - Calderón Delgado, Manuel (University of Dundee, 2021)
The incidence of cutaneous squamous cell carcinoma (SCC) has increased in recent years, while it remains as an understudied subject. Current methods for the diagnose of skin cancer are either invasive, present a low resolution, or images that are difficult to interpret. Full-field optical coherence tomography (FF-OCT) has proven its potential as a non-invasive imaging technique of epithelial tissue. The sub-micrometer resolution offered by FF-OCT is able to show fine features such as cell nuclei, blood vessels, and fibrous structures in the dermis. However, not many physicians are familiar with the images derived from this technique. Using a well-known mouse model of SCC, we acquired volumetric data from skin samples at different stages of the disease using our home-made FF-OCT system. We present OCT-Mouse Skin (OCT-MoS) dataset, a curated dataset of 3400 annotated tomograms distributed into four classes, representing different stages in the development of SCC: normal, dysplasia, papilloma, and SCC. This dataset has a high potential for reuse in areas such as cancer research, medical training, image processing, and deep learning.
Abdominal skin from FVB/N mice was untreated to serve as control samples for the normal class. Back skin from FVB/N mice was treated with immunosupresant and tumor promoter solutions to study different stages of cutaneous squamous cell carcinoma. All samples were excised and imaged by full-field optical coherence tomography.
Keywords: FOS: Biological sciences